Antibiotic stewardship in community pharmacies a scoping review - Jamshed, Shazia (MDPI, 2018)
The increase in antibiotic resistance has frequently been linked to unrestrained antibiotic dispensing. This review was conducted to mainly assess the perception and attitudes of community pharmacists towards antibiotic dispensing. This scoping review was performed between June 2016 and September 2016 to identify published studies related to the perception and attitudes of community pharmacists towards antibiotic dispensing. The combination of terms such as ‘antibiotic dispensing’, ‘antimicrobial resistance’, ‘community pharmacy’, and ‘community pharmacists’ were searched in electronic databases such as PubMed, ProQuest, Google Scholar, and Science Direct. Only published articles within the last 12 years were included. A total of 13 studies were identified. In general, community pharmacists have good awareness and knowledge of antibiotic dispensing. However, the majority of them are still selling antibiotics to their customers and/or patients for unjustified reasons. The community pharmacists seem well aware of the antimicrobial resistance crisis and considered it a significant health issue. However, many embraced the concept that dispensing antibiotics without medical prescription (DAwMP) can be one of the key features in the dissemination of multidrug resistant bacteria.